RANCANG BANGUN SPECTROSCOPY OPTIK PORTABEL BERBASIS ARDUINO MICRO - I Gede Yogi Astawan; Yoga Divayana; Pratolo Rahardjo (Program Studi Teknik Elektro UNUD, 2019)
This research is conducted to build portable spectroscopy optic with Android and desktop applications. Portable spectroscopy optic consists of Arduino Micro, Nextion Liquid Crystal Display (LCD), 2 pieces Light Emitting Diodes (LED), servo motor, diffraction grating (600 lines/mm), 2 pieces photodiodes, Bluetooth HC-05, and SD Card Reader Writer. Android and desktop applications realized by using Qt IDE. Spectroscopy testing is done using polymers with color red, green, and blue. The result of polymers sample testing shows that the spectrum with same wavelength range as the sample color will be passed, while other wavelengths will be absorbed. The device has been able to measure absorption of sample. On testing restore the test results to the SD card produces file with size about 2 kB. Device uses battery with capacity 3000 mAh and can be actively sustainable during 3 hours 31 minutes. Testing of communication Android and desktop applications with spectroscopy is done using bluetooth and Universal Serial Bus (USB) cable. The result of application testing are already able to send and receive data from spectroscopy.